Monetary policy rule in the presence of persistent excess liquidity : the case of Trinidad and Tobago - Birchwood, Anthony ([Caribbean Centre for Money and Finance] [St. Augustine]TT, 2009)
Examines the reliability of the monetary policy rate to effect changes in market interest rates and therefore on aggregate demand in the presence of chronic excess liquidity in an embryonic money market as is the case of Trinidad and Tobago.